Human Resource Planning, Employee Placement, Job Analysis of Employee Performance (Literature Review) - Sardi, Muhammad Arif; Galinging, Apriana Novita Yoman (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human resource planning is crucial for companies to optimize performance, both for the company and for employees. Job analysis is one of the strategies and benchmarks for optimizing employee performance. This research is based on literacy studies from several journals and articles reviewed by the research team. The research results prove that based on studies human resource planning has a significant positive effect on employee performance. However, it turns out that job analysis has a positive but not crucial effect on employee performance. There are other factors that cause this.Human resource planning is crucial for companies to optimize performance, both for the company and for employees. Job analysis is one of the strategies and benchmarks for optimizing employee performance. This research is based on literacy studies from several journals and articles reviewed by the research team. The research results prove that based on studies human resource planning has a significant positive effect on employee performance. However, it turns out that job analysis has a positive but not crucial effect on employee performance. There are other factors that cause this.